Evidence for Griffiths phase in multiferroic BiMnO3 and BiFe0.5Mn0.5O3 films - Prokhorov, V.G.; Kaminsky, G.G.; Kim, J.M.; Yoo, Y.J.; Lee, Y.P.; Svetchnikov, V.L.; Levchenko, G.G.; Nikolaenko, Yu.M.; Khokhlov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Microstructure and magnetic properties of the BiMnO3 and BiFe0.5Mn0.5O3 films, prepared by the rf magnetronsputtering on LaAlO3 (001) single-crystalline substrate, have been investigated. The selected-area electrondiffraction analysis allows us to indentify the crystal structure of the BiMnO3 film as an orthorhombic one whilethe BiFe0.5Mn0.5O3 film has a hexagonal lattice symmetry. The high-resolution electron microscopy study reveals the presence of strip-domain phase with a periodic spacing of about 3c in both films. The magnetic measurements show that in addition to the basic paramagnetic phase, the films manifest the Griffiths phase behaviorin a wide temperature range. We argue that the observed weak ferromagnetism is provided by an appearance of the strip-domain layered inclusions rather than the intrinsic physical origin of the films.